Relationship between V.O2max and repeated sprint ability using non-motorised treadmill ergometry - Brown, P. I.; Hughes, M. G.; Tong, R. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: The aim of this study was to investigate the relationship between maximal oxygen uptake (VO2max) and repeated sprint ability (RSA) using non-motorised treadmill ergometry. Methods: Ten male participants (mean [standard deviation] VO2max: 57.5 [2.1] mL/kg.min) completed a RSA test (10, 6-s sprints with 34-s recovery) on a non-motorised treadmill. Oxygen consumption (VO2) and heart rate (HR) were measured during the RSA test and the decrement of performance fatigue (%d) was calculated for the performance indices mean maximal speed (MxSp) and average power output (AvPO). Results: There were significant relationships between VO2max and the %d MxSp (r=-0.75, P<0.05) and VO2max and the %d AvPO (r=-0.69, P<0.05). There were also significant relationships between VO2max and HR recovery (r=0.56, P<0.05) and VO2max and VO2 recovery (r=0.7, P<0.01). However, while no significant relationships were reported between HR recovery and %d MxSp (r= 0.45, P>0.05) and HR recovery and %d AvPO (r=-0.52, P>0.05), significant relationships were observed between V.O2 recovery and %d MxSp (r=-0.75, P<0.05) and between VO2 recovery and %d AvPO (r=-0.77, P<0.05). Conclusion: The findings of this study suggest that V.O2max may be an important factor determining RSA during repeated, high-intensity running-based exercise, such as field hockey, rugby and soccer.